Institutional quality, knowledge spillovers and entrepreneurship. (1st January 2011) - Chipalkatti, Niranjan; Doh, Jonathan P.; Rishi, Meenakshi
We examine the impact of institutional quality on early stage and formal entrepreneurial activity and on knowledge spillovers. We use four institutional variables – the protection of property rights, business freedom, financial depth, and corruption as proxies for institutional quality. Results suggest that financial institutions matter for formal and early-stage entrepreneurship. Corruption deters formal entrepreneurship, but the presence of corrupt institutions positively influences the conversion of early-stage entrepreneurial entities into formal business ventures. The presence of scientific knowledge in the public domain encourages the knowledge spillover process to early stage entrepreneurs but is retarded by a strong legal and regulatory environment.